Splenectomy in childhood for non‐malignant haematologic disorders – long‐term follow‐up shows minimal adverse effects. (28th April 2020) - Yacobovich, Joanne; Barzilai‐Birenboim, Shlomit; Steinberg‐Shemer, Orna; Stark, Pinhas; Pazgal, Idit; Tamary, Hannah
Summary: Splenectomy is considered therapeutic in various non‐malignant haematologic diseases. Adverse events ‒ specifically infections and thromboembolism ‒ are not extensively documented in the paediatric population, maintaining the concern over risks‐versus‐benefits of the procedure. We studied a cohort of paediatric haematology patients undergoing splenectomy between 1977 and 2015 to determine short‐ and long‐term complications. We summarised all the patients of the haematology clinic in our major Israeli tertiary centre undergoing splenectomy for therapeutic reasons, capturing infectious and thromboembolic events. The data of 103 patients, comprising 1657 follow‐up years, were analysed. The cohort included 33 patients with transfusion‐dependent thalassaemia, seven with non‐transfusion‐dependent thalassaemia, four with sickle‐thalassaemia, 41 with hereditary spherocytosis, and 18 with immune thrombocytopenia. Standard presplenectomy vaccinations were noted in most. No typical cases of overwhelming postsplenectomy infection (OPSI) were identified, nor were typical OPSI bacteria isolated. Thalassaemics with central lines were most prone to infection and thrombosis. Beyond this subgroup, thrombotic events were anecdotal. This is the largest study to date to comprehensively analyse infectious and thrombotic complications of childhood splenectomy for the treatment of haematologic diseases. The use of splenectomy appears to be a relatively safe therapeutic option in paediatric patients with proper preoperative vaccination and follow‐up care; use of central venous lines or catheters increase the risk in thalassaemic patients and should be avoided if possible.